Phosphorous Application Improves Drought Tolerance of Phoebe zhennan - Tariq, Akash; Pan, Kaiwen; Olatunji, Olusanya A.; Graciano, Corina; Li, Zilong; Sun, Feng; Sun, Xiaoming; Song, Dagang; Chen, Wenkai; Zhang, Aiping; Wu, Xiaogang; Zhang, Lin; et al. (Frontiers in Plant Science, 2017)
Phoebe zhennan (Gold Phoebe) is a threatened tree species in China and is a valuable and important source of medicine and wood. Apart from anthropogenic disturbances, several biotic constraints are restricting its growth and development. However, less attention has been given to build adaptive strategies for its proper conservation through examining its morphological and physio-biochemical responses to drought stress, and the role of fertilizers on these responses. A complete randomized experimental design was used to investigate the effects of two levels of water (well-watered and drought-stressed) and phosphorous fertilization treatments (with and without P) to assess the morphological and physio-biochemical responses of P. zhennan seedling to drought stress. In addition, we evaluated whether P application could mitigate the negative impacts of drought on plant growth and metabolism. Drought stress had a significant negative effect on the growth and metabolic processes of P. zhennan; however, reduced leaf area (LA), limited stomatal conductance (Gs), reduced transpiration rate (E), increased water use efficiency (WUEintr), enhanced antioxidant enzymes activities and accumulation of osmolytes suggest the species has good adaptive strategies for tolerating drought stress. Phosphorus application had a significant positive effect on root biomass (RBM), signifying its improved water extracting capacity from the soil. Moreover, P fertilization significantly increased leaf relative water content (RWC), net photosynthetic rate (Pn) and maximal quantum efficiency of PSII (Fv/Fm) under drought stress conditions that could be attributed to several factors, such as enhanced root biomass, the up-regulation of chloroplast pigments, osmolytes, and nitrogenous compounds, and decreased malondialdehyde contents. However, P application had only a slight or negligible effect on the growth and metabolism on well-watered plants. In conclusion, P. zhennan has strong drought resistant potential while P application facilitates and improves tolerance potential mostly through physio-biochemical adjustments, regardless of water availability. It is imperative to explore underlying metabolic mechanisms and effects of different levels of P fertilization in drought condition on P. zhennan for designing appropriate conservation and management strategies for this species at risk of extinction.